Social dimension of work organization: its impact on burnout syndrome - Bermudez, Héctor L.; Benjumea Calderón, Diana Marcela; Córdoba Toro, Daniela (Revista Colombiana de Ciencias Sociales, 2025)
Burnout Syndrome is classified in Colombia as an occupational disease. However, its diagnosis and treatment remain unclear, mainly because organizations tend to identify burnout through individual factors and fail to modify the underlying conditions of work organization—particularly power relations and hierarchical structures. The purpose of this study was to examine the extent to which the social dimension of work organization influences the emergence and development of Burnout Syndrome. Method: Testimonial accounts obtained through in-depth interviews with individuals who had experienced this syndrome were analyzed using a qualitative approach, emphasizing the mental and physical health impacts that burnout caused in each participant. Results: Emotional exhaustion manifested through continuous fatigue, apathy, distress, among other symptoms. Conclusion: As long as the social dimension of work organization remains unchanged, burnout and the disabling suffering it generates will persist.